Gold Nanorod Hydrogel Film for Laser‐Induced Hyperthermic Intraperitoneal Chemotherapy to Treat Peritoneal Malignancies. Issue 10 (31st July 2021) - Court, Karem A.; Yu, Hangjin; Chan, Diana; Blanco, Elvin; Ziemys, Arturas; Holder, Ashley M.
Abstract : Treatment of peritoneal surface malignancies with cytoreductive surgery and HIPEC (CRS/HIPEC) has a substantial risk of local recurrence and causes off‐target toxicity. HIPEC is reinvented utilizing a gold nanorod (GNR) platform to provide surgically targeted precision delivery of mild hyperthermia (42 °C) to increase chemotherapeutic efficacy and reduce off‐target toxicity. A biocompatible hydrogel film containing GNRs, mitomycin‐C (MMC), and cisplatin (CisPt) is designed to create controlled, mild hyperthermia generated from NIR laser treatment of GNRs. The concentration of GNRs and duration of hyperthermia is determined using dose‐response curves to titrate goal temperature parameters of mild hyperthermia (42 °C) in a controlled fashion. Loading and release of CisPt and MMC at an inhibitory concentration (IC50) dose is determined to be highly efficient. In vitro and in vivo experiments demonstrate cytotoxicity and reduced tumor growth in murine models of peritoneal malignancy with preferential accumulation of GNRs within peritoneal tumors. Preclinical evidence of efficacy utilizing a biocompatible hydrogel GNR/MMC/CisPt film can lead to clinical trials in patients with peritoneal malignancies. If successful, treatment of other cancers can benefit from this GNR chemotherapy hydrogel film as a method to decrease the incidence of local recurrence in any surgical resection bed. Abstract : Treatment of peritoneal surface malignancies with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy has substantial risk of local recurrence and causes off‐target toxicity. The in vitro and in vivo performance of a gold nanorod hydrogel film that can be applied by surgeons to deliver mild hyperthermia and chemotherapy is reported. This novel blend of technology with biocompatibility can optimize patient outcomes.